A randomised comparative study to compare the prophylactic use of phenylephrine and norepinephrine in caesarean delivery under spinal anaesthesia - C V Soabir Ali; Jeetendra Kumar Bajaj (Wolters Kluwer Medknow Publications, 2023)
Background: To compare the efficacy and safety of prophylactic intravenous infusions of phenylephrine (0.1 μg/kg/min) and norepinephrine (NE) (0.05 μg/kg/min) for the management of maternal hypotension under spinal anesthesia for cesarean delivery. Methods: A prospective randomized comparative interventional study was conducted on 100 pregnant patients who underwent elective/emergency cesarean section under the sub-arachnoid block. The study patients were randomly allocated into two equal groups comprising of Group P (n = 50): who received phenylephrine 0.1 μg/kg/min infusion prophylactically and Group N (n = 50): who received norepinephrine 0.05 μg/kg/min infusion prophylactically. The data of outcome measures were compared among the two groups by SPSS ver 21.0. Results: A significant difference was seen in the incidence of bradycardia between groups P and N (20% vs 4%, P value = 0.028). The blood pressure was significantly higher in Group N (systolic-120.5 vs 104 mm of Hg, P = 0.026; diastolic-66 vs 61 mm of Hg, P = 0.019). Group N patients had no complications whereas Group P patients experienced nausea (8%) and vomiting (4%), P = 0.027. Neonatal outcomes in terms of Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) score and umbilical arterial/venous blood gases were similar among the two groups (P > 0.05). Conclusion: In conclusion, the study results show that NE is better in maintaining the hemodynamic parameters (BP and HR) during spinal anesthesia for cesarean delivery with minimal side effects. It can be suggested that NE may be advantageous in pregnancies especially those complicated with pregnancy-induced hypertension.